Investigation into a national outbreak of STEC O157:H7 associated with frozen beef burgers, UK, 2017 - Byrne, Lisa; Kaindama, Lukeki; Bentley, Maria; Jenkins, Claire; Aird, Heather; Oliver, Isabel; Paranthaman, Karthik (Epidemiology and infection, 2020)
In November 2017, Public Health England identified an outbreak of Shiga toxin-producing Escherichia coli O157:H7 in England where whole genome sequencing results indicated cases were likely to be linked to a common source, and began investigations. Hypothesis generation included a review of enhanced surveillance data, a case-case study and trawling interviews. The hypothesis of interest was tested through the administration of focussed questionnaires and review of shopping history using loyalty card data. Twelve outbreak cases were detected, eight were hospitalised and four developed haemolytic uraemic syndrome. Frozen beef burgers supplied by a national retailer were identified as the vehicle of the outbreak. Testing of two left-over burger samples obtained from the freezers of two separate (unlinked) cases and a retained sample from the production premises were tested and found to be positive for the outbreak strain. A voluntary recall of the burgers was implemented by the retailer. Investigations at the production premises identified no contraventions of food safety legislation. Cooking guidance on the product packaging was deemed to be adequate and interviews with the cases/carers who prepared the burgers revealed no deficiencies in cooking practices at home. Given the long-shelf life of frozen burgers, the product recall likely prevented more cases.